Motivations for lifelong learning - Syed Ahmad, Tuan Sarifah Aini; Wan Mustapha, Wan Zumusni; Hasan, Nor Haniza; Soo, Kum Yoke (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Lifelong learning is a voluntary, continuous pursuit of knowledge for personal or professional enrichment, driven by internal curiosity and external needs. It goes beyond acquiring skills to support personal growth, adaptability, and societal progress. Key motivations include overcoming challenges in a changing environment, where humans use innate problem-solving abilities and curiosity to deepen understanding and generate new knowledge, as well as the pursuit of self-actualization through exploring diverse subjects, gaining new skills, and reflecting critically on one’s beliefs. These factors collectively sustain individuals’ commitment to ongoing intellectual development.